Toxigenic Genes, Pathogenic Potential and Antimicrobial Resistance of Bacillus cereus Group Isolated from Ice Cream and Characterized by Whole Genome Sequencing - Rosa Fraccalvieri; Angelica Bianco; Laura Maria Difato; Loredana Capozzi; Laura Del Sambro; Domenico Simone; Roberta Catanzariti; Marta Caruso; Domenico Galante; Giovanni Normanno; Lucia Palazzo; Maria Tempesta; et al. (Foods, 2022)
Bacillus cereus is isolated from a variety of foods where it may cause food spoilage and/or food poisoning due to its toxigenic and pathogenic nature. In this study, we identified members of B. cereus groups in 65% of the ice cream samples analyzed, which were characterized based on multi locus variable number tandem repeats analysis (MLVA) and whole genome sequencing (WGS). The MLVA revealed that 36 strains showed different allelic profiles. Analyses of WGS data enabled the identification of three members of the B. cereus group: B. cereus sensu stricto, B. mosaicus and B. thuringiensis. Based on the multi locus sequence typing (MLST) scheme, the strains were classified in 27 sequence types (STs), including ST26 that causes food poisoning. Toxin genes’ detection revealed the presence of the genes encoding nonhemolytic enterotoxin (NHE), hemolysin BL (HBL), cytotoxin K (cytK) and cereulide (ces) in 100%, 44%, 42% and 8% of the strains, respectively. The identification of eleven antimicrobial resistance (AMR) genes predicted the resistance to five different antimicrobials, and the resistance to beta-lactam antibiotics was confirmed with a phenotypic antimicrobial test. Taken together, the results showed that the B. cereus strains isolated from ice cream were a potential hazard for consumer safety.